Hydrothermal Synthesis, Impedance and Optical Properties of Tm-Doped SrBi2Nb2O9 Ceramics - Mohamed Afqir; Stevan Stojadinović; Mohamed Elaatmani; Abdelouahad Zegzouti; Nabiha Tahiri; Mohamed Daoud (Archives of Metallurgy and Materials, 2022)
In this study, Strontium Bismuth Niobate (SrBi2-xTmxNb2O9 with 0 ≤ x ≤ 0.1) doped by Tm was synthesized using by the hydrothermal method. The microstructure and electrical properties were mainly investigated. XRD analysis showed a single-phase orthorhombic structure for Tm-doped SrBi2Nb2O9 samples. The crystallite size is anisotropic and the strain is apparently independent of Tm amount. Dielectric properties for doped SrBi2Nb2O9 with Tm3+ ion have the same trend discussed for the pure sample. FTIR resulats showed that NbO6 octahedral is formed, on one hand, and on the other hand, it shows that spectras for doped and undoped samples are nearly the same. The Cross-section of ceramics showed the plate-like morphology, also the distribution of the pore in ceramics are observed for all samples. Tm dopants produce only minor changes in the impendence parameter values at room temperature. The luminescent (PL) properties of Tm-doped SrBi2Nb2O9 ceramic powders were investigated. The optimum Tm3+ concentration for the maximum PL intensity was found to be at x = 0.075.